Mucosal Immunoregulatory Properties of Tsukamurella inchonensis to Reverse Experimental Food Allergy - Smaldini, Paola L.; Trejo, Fernando M.; Rizzo, Gastón P.; Comerci, Diego J.; Kampinga, Jaap; Docena, Guillermo H. (Frontiers in Immunology, 2021)
The intestinal mucosa is lined by epithelial cells, which are key cells to sustain gut homeostasis. Food allergy is an immune-mediated adverse reaction to food, likely due to defective regulatory circuits. Tsukamurella inchonensis is a non-pathogenic bacterium with immunomodulatory properties. We hypothesize that the anti-inflammatory effect of dead T. inchonensis on activated epithelial cells modulates milk allergy through the restoration of tolerance in a mouse model. Epithelial cells (Caco-2 and enterocytes from mouse gut) and macrophages were stimulated with T. inchonensis and induction of luciferase under the NF-κB promoter, ROS and cytokines production were studied. Balb/c mice were mucosally sensitized with cow´s milk proteins plus cholera toxin and orally challenged with the allergen to evidence hypersensitivity symptoms. After that, mice were orally administered with heat-killed T. inchonensis as treatment and then challenged with the allergen. The therapeutic efficacy was in vivo (clinical score and cutaneous test) and in vitro (serum specific antibodies and cytokines-ELISA, and cell analysis-flow cytometry) evaluated. Heat-killed T. inchonensis modulated the induction of pro-inflammatory chemokines, with an increase in anti-inflammatory cytokines by intestinal epithelial cells and by macrophages with decreased OX40L expression. In vivo, oral administration of T. inchonensis increased the frequency of lamina propria CD4+CD25+FoxP3+ T cells, and clinical signs were lower in T. inchonensis-treated mice compared with milk-sensitized animals. In vivo depletion of Tregs (anti-CD25) abrogated T. inchonensis immunomodulation. In conclusion, these bacteria suppressed the intestinal inflammatory immune response to reverse food allergy.